Ice Crystal Growth in Sucrose Solutions Containing Kappa- and Iota-Carrageenans - KIRAN YILDIRIM, BERÇEM (WILEY-V C H VERLAG GMBH, 2020)
Measurements of ice recrystallization inhibition (IRI) and thermal hysteresis (TH) activities of kappa (kappa)- and iota (iota)-carrageenans were carried out to examine whether they can be novel cryoprotectants or not. IRI measurements indicate that both carrageenans reduce recrystallization in sucrose solution, but that the IRI activity of kappa-carregeenan is higher than that of iota-carrageenan. TH measurements indicate that kappa- and iota-carrageenans do not exhibit TH activity. TH activity measurements of antifreeze glycoprotein (AFGP) in the presence of kappa-carregeenan demonstrate that this carregeenan neither influences the TH activity of AFGP nor the shape of the ice crystals. The round ice crystal shape transformed into an angular and elongated shape in the presence of both carregeenans.
Keywords: Carrageenans; Cryoprotectant; Ice crystals; Ice recrystallization inhibition; Thermal hysteresis; RECRYSTALLIZATION INHIBITION-ACTIVITY; ANTIFREEZE PROTEIN; CELLS